LC-MS Lipid Profiling of the Blood Plasma of Alzheimer’s Patients from Two Communities: African American and Nigerian Populations - Loubna A. Hammad; Yuening Zhang; Katie Lane; Kathleen S. Hall; Jonathan Karty (My University, 2011)
This work is part of the Indianapolis-Ibadan Dementia Project, which is a comparativeepidemiological study examining risk factors for Alzheimer disease (AD) and dementia in twocommunity dwelling elderly populations, Yoruba living in Ibadan Nigeria and AfricanAmericans living in Indianapolis. Previously, a significant relationship between cholesteroland apolipoprotein E genotype and the risk for AD in both populations had been found.We report in this study the use of liquid chromatography mass spectrometry to profile lipidsin the blood plasma of 63 subjects from the two populations. The differences in lipid profilesbetween AD and healthy individuals among the two populations were found using statisticalanalysis tools and the identities of the variant lipids were elucidated.

This work is part of the Indianapolis-Ibadan Dementia Project, which is a comparativeepidemiological study examining risk factors for Alzheimer disease (AD) and dementia in twocommunity dwelling elderly populations, Yoruba living in Ibadan Nigeria and AfricanAmericans living in Indianapolis. Previously, a significant relationship between cholesteroland apolipoprotein E genotype and the risk for AD in both populations had been found.We report in this study the use of liquid chromatography mass spectrometry to profile lipidsin the blood plasma of 63 subjects from the two populations. The differences in lipid profilesbetween AD and healthy individuals among the two populations were found using statisticalanalysis tools and the identities of the variant lipids were elucidated.
LC-MS Lipid Profiling of the Blood Plasma of Alzheimer’s Patients from Two Communities: African American and Nigerian Populations